Contribuições do Programa Cultura Viva na luta pelo reconhecimento: arte-educação para a cidadania no caso do Centro de Referência Integral do Adolescente - Andrade, Mirnah Leite Medeiros Mascarenhas (2017)
This research aims to reflect about the contribution of a cultural policy in the struggle for recognition of minority groups. For that, Cultura Viva program is analyzed in its trajectory, conceptual frame works and impact on the lives of beneficiaries people, while contextualized in the history of Brazilian cultural policies. Based on the Theory of Recognition, it seeks to understand how the Brazilian State has related, throughout the twentieth century, to the cultural production of minority groups and how it approached the idea of cultural diversity, to encompass as the conquest of the cultural rights has been consolidating and contributing to the practice of a new cultural policy in the country since the 21st century, making possible the implementation of the Program. The practices of Centro de Referência Integral do Adolescente (Center for Integral Referral for Adolescents) are taken as a studying case, since an analysis of this cultural policy requires a look at its macro and micropolitical dimensions. It seeks to demonstrate that Cultura Viva, by recognizing, promoting and financing the actions of previously invisible agents, contributes to an institutional recognition and a recognition related to social esteem and subjectivity by providing experiences that enable subjects to “positively refer themselves to their concrete properties and capabilities” (HONNETH, 2003).